Burnout and coping an investigation into the coping styles employed by women religious in the Catholic Church - Carter, Pamela Joy (My University, 1991)
This study investigates the coping style employed by people in the helping professions, who are experiencing the phenomenon known as Burnout. Burnout is conceptualized as one of the serious negative. sequelae of prolonged stress evolved by demanding occupational situations which involve work with people. Investigation is made of the hypothesis that the coping behaviours a person employs in response to stress will be influenced by degree of burnout reported. It was found that emotion focused coping is positively correlated with emotional exhaustion and depersonalization - burnout components. problem focused coping is positively correlated with a second coping style, that of seeking social support.
A dissertation submitted to the Faculty of Arts, University of the Witwatersrand Johannesburg, in partial fulfillment of the requirements for the degree of Master of Arts in Clinical Psychology. Johannesburg, June, 1991.
Keywords: Burn out (Psychology)--Religious aspects; Stress (Psychology)--South Africa; Women in the Catholic Church--South Africa